Impact of Parenting Patterns Against Early Marriage - Suharti, Welza (International Journal of Research in Counseling, 2024)
This article explores the impact that parents' parenting styles have on the tendency for early marriage in their children. In-depth research has revealed that parents' approach to raising children can have a major influence on children's perspectives, decisions and attitudes towards marriage in the future. From a rigid authoritarian parenting style to a supportive authoritative approach, as well as a permissive parenting style that tends to be loose, this article discusses how each of these parenting styles can shape a child's view of the institution of marriage. The analysis also includes the influence of family communication, the values that instilled, as well as the level of parental involvement in the child's life regarding marriage preparations. A number of relevant studies and scientific findings will be described to support the claim that parenting styles play a crucial role in encouraging or inhibiting the tendency for early marriage. This article seeks to provide a better understanding of how parental parenting styles can form the basis of children's decisions regarding marriage. The conclusion of this article provides in-depth thoughts about efforts that can be made, both in family education and parental guidance, to form parenting patterns that support their children to make more mature marriage decisions in the future.